2020
DOI: 10.1002/anie.202009634
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Organometallic Route to Molecular Spin Qubits: The [CpTi(cot)] Case

Abstract: The coherence time of the 17‐electron, mixed sandwich complex [CpTi(cot)], (η8‐cyclooctatetraene)(η5‐cyclopentadienyl)titanium, reaches 34 μs at 4.5 K in a frozen deuterated toluene solution. This is a remarkable coherence time for a highly protonated molecule. The intramolecular distances between the Ti and H atoms provide a good compromise between instantaneous and spin diffusion sources of decoherence. Ab initio calculations at the molecular and crystal packing levels reveal that the characteristic low‐ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 60 publications
(24 reference statements)
2
52
0
Order By: Relevance
“…5,6 The interest in the magnetic properties of sandwich organometallic compounds has considerably grown in the last few years, also for applications as molecular spin qubits. 7–9 Layfield et al reported a dysprosium metallocene cation [(Cp iPr5 )Dy(Cp*)] + showing an exceptionally high anisotropy barrier U eff of 1541 cm −1 , and its 100 s blocking temperature T B is 65 K. 10 In 2022, Long, et al just reported one dilanthanide complex with metal–metal bonding whose energy barrier and blocking temperature are up to 1631 cm −1 and 72 K, respectively. 11 Recently, we also theoretically predicted that the energy barrier and blocking temperature of one two-coordinate [Co(C(SiMe 2 ONaphthyl) 3 ) 2 ] 12 can be enhanced up to 1559.1 cm −1 and 90 K, respectively, through the structural distortion.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The interest in the magnetic properties of sandwich organometallic compounds has considerably grown in the last few years, also for applications as molecular spin qubits. 7–9 Layfield et al reported a dysprosium metallocene cation [(Cp iPr5 )Dy(Cp*)] + showing an exceptionally high anisotropy barrier U eff of 1541 cm −1 , and its 100 s blocking temperature T B is 65 K. 10 In 2022, Long, et al just reported one dilanthanide complex with metal–metal bonding whose energy barrier and blocking temperature are up to 1631 cm −1 and 72 K, respectively. 11 Recently, we also theoretically predicted that the energy barrier and blocking temperature of one two-coordinate [Co(C(SiMe 2 ONaphthyl) 3 ) 2 ] 12 can be enhanced up to 1559.1 cm −1 and 90 K, respectively, through the structural distortion.…”
Section: Introductionmentioning
confidence: 99%
“…44−58 In addition, the capability to link these qubits to other units make them ideal candidates for the proposed architecture. As a model example, we consider a qubit = g e ∓ Δg/ 2, with Δg = 0.002, g Q = (1.98, 1.98, 1.96), as typical for VO 2+ or Ti 3+ , 42 T 1 = 2 μs, T 2 = 0.5 μs, and T R = 10 μs. Inhomogeneous broadening of the parameters is included by a Gaussian broadening of the peaks with fwhm 2.35 mT.…”
mentioning
confidence: 99%
“…To address these challenges, we and others are employing coordination chemistry to rationally control both the physical and electronic structure as well as coherence properties including quantum state lifetimes ( T 1 ) and coherence times ( T m ). ,, Ligand design provides an immediate route to achieve long T 1 and T m or optical initialization and read-out pathways. Further tuning parameters such as spin–orbit coupling, crystal field splitting, and electron–nuclear hyperfine interaction provide additional handles to optimize the requisite sensor criteria mentioned above. ,,, In addition, harnessing parameters such as spin–orbit coupling and hyperfine interactions can elicit detection of physical parameters beyond magnetic fields, including electric fields and pressure. ,, Lastly, employing anisotropic electronic structures of transition metals can provide orientation information during sensing, enhancing the spatial resolution of the molecular sensor. , …”
Section: Toward the Next Generation Of Quantum Sensorsmentioning
confidence: 99%